The Postition of Village Peace Judges in the Resolution of Traditional Offences within the Tolaki Community in South-East Sulawesi - Harris, Oheo K.; Ukkas, Rustam (UI Scholars Hub, 2019)
This research is aimed at finding the appropriate method for Tribe Leaders (as Judges), guardians of local wisdom in resolving conflicts of interest particularly for indigenous people (Tolakinese) in Southeast Sulawesi. Legally speaking, this effort is essential in gaining legitimacy, hence based on customary law (Adat Law); village judges effectively resolve conflict in a faster, simpler and cheaper ways that are accepted by the community compared to the national criminal justice system. Nowadays, various conflicts often arise in communities, which cause economic, political, religious, ethnic, and self-esteem complications leading to conflicts of interest. Sadly, the Tolaki community is not exempted from this reality. This study seeks to offer an appropriate method of resolving conflict by using a consensus based approach to reach decision so as to create peace for the parties. This concept of consensus in deliberation has been practiced in Tolakinese society for a long time. This study found weaknesses and obstacles in its application of the substantial aspects; i.e. the role of village judges is limited by positive law; as well as from a structural aspect: the lack of institutional strengthening. The application of such methods can create a holistic and integrated policy in controlling and optimizing the source of collective strategic resources for the greatest benefit for greatest number of people.